Penetration of inferior alveolar nerve canal increased by bicortical fixation after bilateral sagittal split osteotomy in mandibular prognathism. Issue 2 (February 2022) - Sinha, S.P.; Duong, T.D.H.; Duy, T.-D.T.; Ko, E.W.-C.; Chen, Y.-R.; Huang, C.S.
Abstract: The purpose of this three-dimensional cone beam computed tomography (CBCT) study was to identify the difference between monocortical fixation (MCF) and bicortical fixation (BCF) in mandibular canal penetration after bilateral sagittal split osteotomy (BSSO) to correct mandibular prognathism, where interosseous fixation was done by BCF or MCF. CBCT was performed 1 week postoperatively and Dolphin 3D software was used to assess direct penetration of the mandibular canal by either type of screw. The primary outcome variable was the presence or absence of mandibular canal penetration and was categorized as a binary coded variable. The BCF and MCF groups were compared by χ 2 test, and the odds ratio for canal penetration was estimated. Multiple logistic regression was performed to identify factors related to canal penetration. A total of 118 patients were included. The MCF group had only 6% canal penetrations (3/50 patients) and the BCF group had 58.8% canal penetrations (40/68 patients). The regression model showed that BCF was the only factor causing mandibular canal penetration, with an adjusted odds ratio of 52.5. Awareness of the increased risk of canal penetration with BCF and potential nerve injury might influence case selection.